Inkonsistensi Norma Hukum Pada Pelaksanaan Pengampunan Pajak (Indonesian Journal of Criminal Law, 2022)
The research objective to analyze the inconsistency of legal norms that occur in the implementation of tax amnesty. This type of research is normative legal research, using a statutory approach (status approach) and a conceptual approach (conceptual approach). The results of this study indicate that (1) Article 21 paragraph 2 of Law no. 11/2016 Regarding TA there is the word "other party" the word is equated with the reporting party. Then what is meant by "prohibited" according to grammatical interpretation. Resolution of the inconsistency of legal norms that exist between Law no. 11/2016 concerning TA and PP No. 43/2015 Regarding PPTPPU, it can be pursued through a constitutional route by conducting a judicial review to the Supreme Court. In addition, the application of legal principles is an important instrument that can provide a role in the process of resolving overlapping regulations. The exact principle of the problem is lex superior derogate lex inferior, meaning that Law no. 11/2016 concerning TA applies and beats the regulations under PP No. 43/2015 concerning PPTPPU. Tujuan penelitian menganalisis inkonsistensi norma hukum yang terjadi pada pelaksanaan pengampunan pajak. Tipe penelitian ini adalah penelitian hukum normatif, dengan menggunakan pendekatan perundang-undangan (status approach) dan pendekatan konseptual (conceptual approach), Hasil penelitian ini menunjukkan bahwa (1) Pasal 21 ayat 2 UU No. 11/2016 Tentang TA terdapat kata “pihak lain” kata tersebut dipersamakan pihak pelapor. Kemudian yang dimaksud dengan “dilarang” menurut interpretasi gramatikal. Penyelesaian inkonsistensi norma hukum yang terdapat antara UU No. 11/2016 Tentang TA dan PP No. 43/2015 Tentang PPTPPU dapat ditempuh dengan jalur konstitusional dengan melakukan uji materi ke Mahkamah Agung. Disamping itu, penerapan asas hukum merupakan sebuah instrumen penting yang dapat memberikan peran dalam proses penyelesaian terhadap regulasi yang tumpang tindih. Asas yang tepat dari permasalahan tersebut adalah lex superior derogate lex inferior, artinya UU No. 11/2016 Tentang TA berlaku dan mengalahkan aturan dibawahnya PP No. 43/2015 Tentang PPTPPU.